Terapi Aktifitas Kelompok Permainan Respon Ekspresi dalam Gambar pada Pasien Skizofrenia (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effectiveness of group activity therapy of response expression games in pictures of schizophrenia patients in the Srikandi room of Dr. Arif Zainuddin Surakarta Mental Hospital. The research method used is quantitative with a pre-experimental approach of one group pre-test - post-test design. The results of this study indicate that there is a significant decrease in scores in 7 respondents before and after the TAK intervention; namely, in Mrs. S, the score before the intervention was 10, and after the intervention, the score dropped to 8, in Mrs. D from a score of 10 dropped to 7, in Mrs. H from a score of 12 dropped to 8, in Mrs. A from a score of 13 dropped to 11, in Mrs. E from a score of 18 dropped to 12, in Mrs. S from a score of 10 dropped to 7, and in Mrs. T from a score of 12 dropped to 7. In conclusion, there is effectiveness in group activity therapy of response expression games in pictures of schizophrenia patients in the Srikandi room of Dr. Arif Zainuddin Surakarta Mental Hospital. Keywords: Image expression, Hallucination, Schizophrenia, Group Activity Therapy